GRUPOS FUNCIONAIS TROFICOS DA TRICOPTEROFAUNA EM RIACHOS DE PEQUENA ORDEM NA RESERVA BIOLÓGICA DE SALTINHO (PERNAMBUCO) - Silva, Rafael Pereira da; Rodrigues, Gilberto Gonçalves (Revista Nordestina de Zoologia, 2017)
The freshwater environments are heterotrophic systems, having almost 100% of their energy derived from the riparian forest, being the allochthonous material of extreme importance for the maintenance of ecosystem processes. The Trichoptera Order is an important component of the freshwater macrofauna, participating in the transfer of energy at all trophic levels. Because they present a wide diversity, they are considered efficient bioindicators and play an important role in the decomposition of organic material in the lotic ecosystems. The present study aimed to evaluate the functional trophic groups in low - order stream of the Saltinho Biological Reserve. The Saltinho stream was subdivided into three independent blocks of 150m. In this study was made experiments of colonization and leaf breakdown of Inga ingoides by macroinvertebrates. During 120 days leaves were colonized by 643 larvae insects of caddies flies that it belong to a all functional trophic groups (FTG). Leptoceridae (~47%) shows the great abundance. The Triplectides is the genus of great abundance because it is associated to shredder habit. Another taxa belong to collectors, scrapers, scraper- collector and scraper- filtrator. In this study the (FTG) shows closed relationship to I. ingoides leaf breakdown and the colonization succession of immature caddy flies. Shredders started the leaf breakdown followed by collectors, scrapers and scrapers-filtrator.